Hakikat Fitrah Manusia dalam Perspektif Pendidikan Islam (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2022)
Since humans are determined to demand progress in their lives, since then education is needed in creating ideas or ideas to develop the potential that exists within them. Historically, education has always accompanied every generation to guide humans to be in accordance with the times. Various kinds of educational curricula have been made based on the theory of education that has been developed, starting from the theory of traditional education, western education, even though Islamic education. Every time the policy makers change, the education curriculum changes too. The fundamental question that needs to be asked is what kind of curriculum is in accordance with the characteristics of the Indonesian nation? This paper will describe a comparison of traditional education, western education and Islamic education. This is done in an effort to avoid unilateral claims that true education is Islamic education. So that the results of this comparison, we can find education with what kind of model is in accordance with human nature.